Nutrition therapy in cachectic cancer patients. The Tight Caloric Control (TiCaCo) pilot trial. (1st August 2015) - De Waele, Elisabeth; Mattens, Sabrina; Honoré, Patrick Maurice; Spapen, Herbert; De Grève, Jacques; Pen, Joeri J.
Highlights: The nutritional status of cancer patients was assessed. Intervention with nutrition therapy or regular diet was done. Patients were randomized after biophysical workup with calorimetry. Nutrition therapy diminishes unexpected hospital stays in cancer patients. Nutrition therapy prolongs overall survival in cancer patients. Abstract: Background: Cancer is a common disease and many patients are diagnosed with advanced stages. Due to cancer generalization, patients may become ill-nourished and even cachectic. Malignancy-related cachexia is associated with worsening physical function, reduced tolerance to anticancer therapy and increased mortality. We assessed the effect of a patient-tailored nutritional approach in newly discovered, treatment-naive cancer patients with cachexia. Methods: In a randomized, single-blinded, controlled pilot study, patients were treated with either intensive, biometric parameter-oriented dietary counseling (nutrition therapy) compared to regular dietary counseling (control), before and during conventional cancer treatment. Twenty patients were enrolled over a one-year period, 10 receiving nutrition therapy and 10 controls. The primary endpoint was recovery of body composition after nutrition therapy. Secondary endpoints declined in morbidity and mortality with nutrition therapy. Results: Average weight evolution in the control group after 3, 6 and 12 months was 0.19 ± 7.87 kg, −9.78 ± 7.00 kg and −5.8 kg, and in the nutrition therapy group 0.69 ± 2.4 kg, 0.77 ± 2.58 kg and 1.29 ± 3.76 kg. Control patients had a significantly longer average hospital stay than subjects from the nutrition therapy group (37.6 vs. 3.4 days). Eight nutrition therapy patients and 1 control patient were still alive after 2 years. Conclusions: Nutrition therapy based on patient-specific biophysical parameters helps to maintain body weight and induces a more optimal nutritional balance in cachectic cancer patients. Moreover, survival in cancer patients improved when their nutritional status, even partially, ameliorated.